Blockade of Electron Transport at the Onset of Reperfusion Decreases Cardiac Injury in Aged Hearts by Protecting the Inner Mitochondrial Membrane - Chen, Qun (Hindawi Publishing Corporation, 2012)
Myocardial injury is increased in the aged heart following ischemia-reperfusion (ISC-REP) compared to adult hearts. Intervention at REP with ischemic postconditioning decreases injury in the adult heart by attenuating mitochondrial driven cell injury. Unfortunately, postconditioning is ineffective in aged hearts. Blockade of electron transport at the onset of REP with the reversible inhibitor amobarbital (AMO) decreases injury in adult hearts. We tested if AMO treatment at REP protects the aged heart via preservation of mitochondrial integrity. Buffer-perfused elderly Fischer 344 24 mo. rat hearts underwent 25 min global ISC and 30 min REP. AMO (2.5 mM) or vehicle was given for 3 min at the onset of REP. Subsarcolemmal (SSM) and interfibrillar (IFM) mitochondria were isolated after REP. Oxidative phosphorylation (OXPHOS) and mitochondrial inner membrane potential were measured. AMO treatment at REP decreased cardiac injury. Compared to untreated ISC-REP, AMO improved inner membrane potential in SSM and IFM during REP, indicating preserved inner membrane integrity. Thus, direct pharmacologic modulation of electron transport at REP protects mitochondria and decreases cardiac injury in the aged heart, even when signaling-induced pathways of postconditioning that are upstream of mitochondria are ineffective.